The Relationship between Digital Literacy and Entrepreneurial Intention in a New Business - Nor Sakinah Saadah Mohamad Rani; Siti Aisyah Salim (Research in Management of Technology and Business, 2024)
Digitization has substantially changed the world, where advanced and innovative digital technologies cause massive implications in every aspect of human life. Consequently, it is not surprising that the spread of digital technologies has created a promising environment for entrepreneurship and has considerably inspired entrepreneurs to use these technologies in the creation of new firms or the execution of commercial operations. Therefore, it is important for us or entrepreneurs to adapt to the development of this digital technology The objective of this study is to identify the relationship between digital literacy and entrepreneurial intention in a new business. Quantitative research by distributing a set of questionnaire through Google Form is used. A total of 229 respondents from UTHM helps in filled in the questionnaire. The data is gathered using a questionnaire and will be quantitatively evaluated using the SPSS software. Descriptive analysis and correlation analysis is used to reach the objectives of this study. All three objectives that has been stated in the early of this study has been achieved. Hence, this research can contribute to enhance the knowledge to the education sector to understand the respondents’ perception on digital literacy towards entrepreneurial intention in a new business.